ACIDIFICATION OF FOREST SOIL FOR DIPTEROCARP PLANTING STOCK PRODUCTION - Kajornsrichon, Sunanta; Kijkar, Somyos (วารสารวนศาสตร์ไทย, 2022)
Acidification of forest soil for 2 Dipterocarp species (Hopea odorata and Shorea roxburghii) for planting stock production was conducted at the ASEAN-Canada Forest Tree Seed Centre, where both soil and water contain high calcium carbonate. The pH of both soil and water is around 8. Acidification treatments had 7 levels : (1) control, (2) addition of sulfur powder at 2.22 kg/m3, (3) addition of sulfur powder at 3.89 kg/m³, (4) addition of sulfur powder at 5.56 kg/m3, (5) addition of aluminum sulfate at 2.78 kg/m3, (6) addition of aluminum sulfate at 5.56 kg/m3 and (7) addition of aluminum sulfate at 8.33 kg/m3. The results showed that for 10 months H. odorata planting stock production, addition aluminum sulfate and sulfur at rate 5.56 kg/m3 and 8.33 kg/m3 respectively, was recommended. However, applying sulfur powder at 3.89 kg/m3 was enough for producing 7-month seedlings. The average survival percentage was 91.83. Addition of sulfur powder at the rate of 5.56 kg/m3 was recommend for S. roxburghii planting stock production. The survival percentage was 49.03. Acidification at every level had no effect on seedling survival of both species. Improving soil characteristics to improve survival rate of S. roxburghii in alkaline conditions should continue to be studied.